2007
DOI: 10.1002/crat.200711024
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of Nd, Yb – yttrium oxide nanopowders obtained by sol‐gel method

Abstract: Nanopowders of Y 2 O 3 pure, doped and codoped by Nd 3+ , Yb 3+ were obtained by sol-gel method. Solution with ethylene glycol was choosed as the proper solution where crystallites of powder with Nd and Yb dopants had the same size. Finally the one-phased compounds of Y 2 O 3 doped 0.5 at% Nd and 1, 2 or 4 at% Yb were obtained. Grain growth and their morphology were investigated in various temperature and time of heating. The changes of crystallite sizes and lattice constants in relation to the heating time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It is shown that the maximum Yb 3+ emission intensity is attained by having 0.5% Nd and 2.0% Yb. This result correlates well with the results found by Rzepka et al [6]. At half the optimum doping levels, the spectral signature is comprised entirely of Nd 3+ emission indicating that energy transfer is not occurring.…”
Section: Fluorescencesupporting
confidence: 91%
“…It is shown that the maximum Yb 3+ emission intensity is attained by having 0.5% Nd and 2.0% Yb. This result correlates well with the results found by Rzepka et al [6]. At half the optimum doping levels, the spectral signature is comprised entirely of Nd 3+ emission indicating that energy transfer is not occurring.…”
Section: Fluorescencesupporting
confidence: 91%
“…Unfortunately, it appears that the emission characteristics of luminescent ions in these materials depend crucially on the method of preparation [17]. In this work we present results of spectroscopic investigation of neodymium doped GGG nanocrystals obtained by modified sol-gel process which was successfully applied for preparing the nanopowder of yttrium aluminium garnet (YAG), yttrium oxide (YO) and calcium gadolinium oxyborates (CGOB) [19][20][21]. In contrast to synthesis described in [15][16][17] the acetic acid was used as complexing agent instead of citric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, considerable interest in the field of luminescent materials has been the focus of nanomaterials doped with lanthanide ions, these nanomaterials exhibit attractive chemical features such as blinking, low toxicity, resistance to photochemical degradation, and photobleaching. To the best of our knowledge, most of the available preparation involving the sol–gel method, hydrothermal process, the Pechini method, and solvothermal synthesis give excellent opportunities to obtain lanthanide-doped nanomaterials with various particles sizes, shapes, and doping levels, and these parameters greatly influence the chemical activity and luminescent properties of such materials.…”
Section: Introductionmentioning
confidence: 99%